Functional Analysis of CPSF30 in Nilaparvata lugens Using RNA Interference Reveals Its Essential Role in Development and Survival - Shengli Jing; Jing Yang; Yali Liu; Feifei Wang; Fang Zheng; Aobo Ren; Bingbing Yu; Yue Zhao; Bing Jia; Ruixian Chen; Bin Yu; Qingsong Liu; et al. (Insects)
The brown planthopper (Nilaparvata lugens) is a major pest threatening global rice production, significantly reducing yields annually. As N. lugens increasingly develops resistance to conventional control methods, such as chemical pesticides, there is an urgent need for innovative and sustainable pest management strategies. Cleavage and Polyadenylation Specificity Factor 30 (CPSF30) is a key protein involved in mRNA 3′ end processing, yet its function in N. lugens remains poorly understood. This study aims to elucidate the role of CPSF30 in the growth and development of N. lugens and evaluate its potential as a target for RNA interference (RNAi)-based pest control strategies. We cloned and characterized the cDNA sequence of NlCPSF30, which encodes a protein of 341 amino acids containing five CCCH zinc-finger domains and two CCHC zinc-knuckle domains. Sequence alignment revealed that NlCPSF30 is highly conserved among insect species, particularly in the zinc-finger domains essential for RNA binding and processing. Phylogenetic analysis showed that NlCPSF30 is closely related to CPSF30 proteins from other hemipteran species. Expression analysis indicated that NlCPSF30 is most highly expressed in the fat body and during the adult stage, with significantly higher expression in females than in males. RNAi-mediated silencing of NlCPSF30 in third-instar nymphs resulted in severe phenotypic abnormalities, including disrupted molting and increased mortality following injection of double-stranded RNA (dsRNA) targeting NlCPSF30. Moreover, it influenced the expression of genes associated with hormone regulation, namely NlHry, NlE93, and NlKr-h1. These results suggest that NlCPSF30 is integral to critical physiological processes, with its disruption leading to increased mortality. Our findings identify NlCPSF30 as an essential gene for N. lugens’ survival and a promising target for RNAi-based pest management strategies. This study provides a valuable molecular target and theoretical insights for developing RNAi-based control methods against N. lugens.